2017
DOI: 10.3390/w9090694
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Seasonal Variation of Biomineral Suspended Particulate Matter Properties in High-Turbid Nearshore and Low-Turbid Offshore Zones

Abstract: Suspended particulate matter (SPM) is abundant and essential in marine and coastal waters, and comprises a wide variety of biomineral particles, which are practically grouped into organic biomass and inorganic sediments. Such biomass and sediments interact with each other and build large biomineral aggregates via flocculation, therefore controlling the fate and transport of SPM in marine and coastal waters. Despite its importance, flocculation mediated by biomass-sediment interactions is not fully understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 53 publications
4
28
0
Order By: Relevance
“…The effect of suspended sediment on the transmission losses can be expected to cause little uncertainties in the sandy and gravelly areas outside the turbidity maximum zone in Belgian waters; it could, however, become moderate to prohibitive in deeper areas or in case of dense plumes of sediments in the water column related to human activities (dredging, trawling). In general, considering jointly the seasonal and spatial variations of SPMc in the BPNS [70], a maximal water depth of~50 m over the region, and the preliminary observations from this investigation, it may be surmised that for the gravelly and sandy clear-water areas (offshore and in the SW nearshore areas), the effect of suspended sediment will always be small, since the highest volume concentrations are to be expected in the lowest layer of the water column, thus involving too short a sound travel path to significantly affect the echo level. Previous investigations on the effect of near-bed SPM on BS for the first study area can be found in [33,54] and actually reported negligible effects.…”
Section: Short-term Backscatter Tidal Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…The effect of suspended sediment on the transmission losses can be expected to cause little uncertainties in the sandy and gravelly areas outside the turbidity maximum zone in Belgian waters; it could, however, become moderate to prohibitive in deeper areas or in case of dense plumes of sediments in the water column related to human activities (dredging, trawling). In general, considering jointly the seasonal and spatial variations of SPMc in the BPNS [70], a maximal water depth of~50 m over the region, and the preliminary observations from this investigation, it may be surmised that for the gravelly and sandy clear-water areas (offshore and in the SW nearshore areas), the effect of suspended sediment will always be small, since the highest volume concentrations are to be expected in the lowest layer of the water column, thus involving too short a sound travel path to significantly affect the echo level. Previous investigations on the effect of near-bed SPM on BS for the first study area can be found in [33,54] and actually reported negligible effects.…”
Section: Short-term Backscatter Tidal Dependencementioning
confidence: 99%
“…Direction and consistency of the trend, regardless of the noise envelope, can be a valuable proxy of change and bypass conflicting results from surveys acquired at different tidal and/or seasonal moments. Interpretation of serial backscatter surveys in such environments should largely benefit both from time series of driving variables (collected via the deployment of benthic landers as in [49,70]) and from regional predictive oceanographic models providing local conditions usable for designing monitoring surveys accordingly.…”
Section: Implications For Repeated Backscatter Mapping Using Mbesmentioning
confidence: 99%
“…Due to the rapid settling of sediment inside the harbor, strong gradients are expected in the size and composition of the remaining SPM. The SPM inside the harbor has larger floc sizes and lower densities with higher organic content, while outside the harbor, the SPM occurs as bio-mineral aggregates as described by Fettweis and Lee (2017). The echo intensity of the backscattered acoustic signal should therefore only be seen as an estimate of the SPM concentration.…”
Section: Spm Concentration Measurements From Adcp Transects Inside Anmentioning
confidence: 99%
“…Their concerns already integrate the natural complexity since Mengual et al [348] relate to erosion of sand-mud mixtures, and Fettweis and Lee [349] to the biological influence on aggregation in coastal waters.…”
Section: Highlights Of Research Papersmentioning
confidence: 99%
“…Fettweis and Lee [349] analyse the variability of aggregates measured in the Belgian coastal waters from 2004 to 2011. Here "aggregate" is preferred to "floc", following the recommendation of Milliman [350] who writes that "flocculation" suggests an electrochemical process and denies biological influences.…”
Section: Highlights Of Research Papersmentioning
confidence: 99%